Beyond the workfare state : labour markets, equalities and human rights / edited by Mick Carpenter, Belinda Freda and Stuart Speeden. - Carpenter, Mick; Freda, Belinda; Speeden, Stuart (Policy Press, 2007)
"Beyond the Workfare State" explores equality, discrimination and human rights in relation to employability and 'welfare-to-work' policies. It draws extensively on new research from the SEQUAL Project, undertaken for the European Social Fund, which investigated seven dimensions of discrimination in a labour market that is theoretically 'open to all'. The book provides an overall analysis of policy shifts and presents a wide and distinctive range of illustrative studies that give voice to a variety of potentially marginalised groups. Chapters deal with obstacles to labour-market access around each of the following themes: gender and class; disability; race and ethnicity; geographical exclusion; sexual orientation; the problems of old and young people; and refugees. The authors draw attention to localised examples of promising practice, but also connect these to a broader 'human rights' agenda, linking them to changing legislative and governance frameworks. Its scope covers the whole of Great Britain and it shows how devolution in Scotland and Wales, and at the regional level in England, is creating new possibilities for mainstreaming good practice in this key area. The book will be of great interest to academics and students in social policy and related fields. It will also be valuable for professionals, policy makers and practitioners in the regeneration, community development and anti-discrimination fields, particularly in the UK but also in Europe and beyond..